Carbon Ion Radiotherapy - Advantages, Technical Aspects and Perspectives - Kubiak, Tomasz (Joint Institute for Nuclear Research, 2013)
Carbon ion radiotherapy is a groundbreaking method of treatment radioresistant tumors situated close to critical organs. The article presents the physical basis of carbon ion therapy, methods of generation and acceleration of heavy ions, systems of forming and exact positioning of the therapeutic beam. Intensity modulated particle therapy and raster scanning technique allow optimum compatibility between the irradiated volume and target volume. By dint of such methods minimum exposure of critical structures is possible. An important aspect of the treatment process is the monitoring of patient's position during the irradiation. It is possible by means of the modern imaging techniques such as PET-CT. Increase of the availability of heavy ion therapy and its development are big challenges for the physicists of the most prestigious research centers in the world.
Keywords: teleradiotherapy; carbon ion therapy; IMPT; raster scanning; tumors